Pediatric Primary Tympanoplasty Outcomes With Autologous and Non-autologous Grafts. Issue 1 (January 2022) - Cass, Nathan D.; Hebbe, Annika L.; Meier, Maxene R.; Kaizer, Alexander M.; Kalmanson, Olivia A.; Stevens, Christina; Tholen, Kaitlyn E.; Haville, Salina; Handley, Elyse; Francom, Christian R.; Herrmann, Brian W.
Abstract : Objective: To compare rates of successful tympanic membrane (TM) closure in primary pediatric tympanoplasty between various autologous and non-autologous tissues. Methods: A retrospective chart review was performed examining all primary pediatric tympanoplasties over a 20-year period at a single institution. Results: In 564 pediatric tympanoplasties, no statistically significant difference existed between success rates of autologous and non-autologous grafts ( p  = 0.083). Compared with fascia, the hazard ratios (and 95% confidence intervals [CI]) for failure for each graft were as follows: human pericardial collagen (HR 0.90, CI 0.54–1.50, p  = 0.680), porcine submucosal collagen (HR 1.07, CI 0.56–2.05, p  = 0.830), human acellular dermal collagen (HR 1.66, CI 0.95–2.87, p  = 0.073), and "multiple grafts" (HR 0.72, CI 0.26–1.98, p  = 0.520). Survival curves demonstrated that 75% of graft failures occurred by 6 months after surgery, the rest occurring between 6 and 12 months postoperatively. Larger perforations encompassing more than or equal to 50% of the TM had lower success rates (HR 1.50, CI 1.02–2.21, p  = 0.041) than smaller perforations encompassing less than 50% of the TM. Age was not correlated with success (HR 0.98, CI 0.93–1.03, p  = 0.390). Conclusion: This study found that non-autologous collagen grafts provide equivalent rates of healing when compared with autologous tissue in primary pediatric tympanoplasty. In addition to the potential for reduced operative time and donor site morbidity, these materials provide a viable graft alternative in fascia-depleted ears. Level of Evidence: Level 4 Abstract : Supplemental Digital Content is available in the text